I survived : the destruction of Pompeii, AD 79 - Tarshis, Lauren; Ball, Georgia (I survived (Graphic novel series), 2024)
"No one in the bustling city of Pompeii worries when the ground trembles beneath their feet. The beast under the mountain Vesuvius, high above the city, wakes up angry sometimes--and always goes back to sleep. But Marcus is afraid. He knows something is terribly wrong--and his father, who trusts science more than mythical beasts, agrees. When Vesuvius explodes into a huge cloud of ash and rocks that fall from the sky like rain, will they have time to escape--and survive the epic destruction of Pompeii? Lauren Tarshis's New York Times bestselling I Survived series comes to vivid life in graphic novel editions. Perfect for readers who prefer the graphic novel format, or for existing fans of the I Survived chapter book series, these graphic novels combine historical facts with high-action storytelling that's sure to keep any reader turning the pages. Includes a nonfiction section at the back with facts and photos about the real-life event"--